How Media Constructs the Image of Marketing, Advertising and PR Professions: A Case Study of The Boys TV Series - Papp-Váry, Árpád; Oltai, Márk (Journal of Cultural Analysis and Social Change, 2025)
Stereotypes continue to shape how marketing, advertising, and public relations (PR) professionals are perceived by society. These simplified and often distorted images influence not only public opinion but also career paths, gender roles, and internal professional identity. This article explores how such representations emerge and persist, with a particular focus on their portrayal in popular media. Drawing on insights from sociology, psychology, media studies, and business ethics, the paper uses The Boys television series as a case study. The show offers a satirical yet insightful depiction of corporate communication, enabling analysis of how professional roles are framed in entertainment. The study incorporates qualitative data from a focus group, in which participants reacted to selected scenes and reflected on their own perceptions and experiences. Findings reveal recurring patterns: PR is associated with manipulation, marketing with persuasion, and advertising with superficiality. Gendered expectations also emerged, with participants identifying structural barriers that limit women’s access to leadership. By linking fictional media content with real-world attitudes, the article highlights the broader cultural impact of entertainment narratives. It emphasizes the importance of fostering more inclusive and accurate portrayals and encourages reflection on how media representations influence both the legitimacy and self-understanding of communication professionals.